2013
DOI: 10.1371/journal.pone.0059483
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Calculus Model of Electrical Impedance Applied to Human Skin

Abstract: Fractional calculus is a mathematical approach dealing with derivatives and integrals of arbitrary and complex orders. Therefore, it adds a new dimension to understand and describe basic nature and behavior of complex systems in an improved way. Here we use the fractional calculus for modeling electrical properties of biological systems. We derived a new class of generalized models for electrical impedance and applied them to human skin by experimental data fitting. The primary model introduces new generalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…Recently it is showed that the fractional model perfectly fits the test data of memory phenomena in different disciplines [46] they have found that a possible physical meaning of the fractional order is an index of memory. From this viewpoint fractional calculus has found many applications in new research on physics of biological structures and living organisms, from DNA dynamics [47][48][49] to protein folding [50], cancer cells [51], tumor-immune system [52], modeling of some human autoimmune diseases such as psoriasis [53], bioimpedance [54], spiking neurons [55], and also the transport of drugs across biological materials and human skin [56] and electrical impedance applied to human skin [57] and even modeling of HIV dynamics [58].…”
Section: Fractional Calculus In Bioscience and Biomedicinementioning
confidence: 99%
“…Recently it is showed that the fractional model perfectly fits the test data of memory phenomena in different disciplines [46] they have found that a possible physical meaning of the fractional order is an index of memory. From this viewpoint fractional calculus has found many applications in new research on physics of biological structures and living organisms, from DNA dynamics [47][48][49] to protein folding [50], cancer cells [51], tumor-immune system [52], modeling of some human autoimmune diseases such as psoriasis [53], bioimpedance [54], spiking neurons [55], and also the transport of drugs across biological materials and human skin [56] and electrical impedance applied to human skin [57] and even modeling of HIV dynamics [58].…”
Section: Fractional Calculus In Bioscience and Biomedicinementioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] The fractional-order differential equations are naturally related to systems with multiple timescale dynamics (related to the complexity of the medium) and memory effects, which exist in most biological systems. [28][29][30][31][32][33][34][35][36][37] Mathematical models involving fractional differential equations have been proven valuable in understanding the dynamics of tumor-immune system and how host immune cells and cancerous cells evolve and interact. Considering the diffusion of drugs in cancer cells and fractality of DNA walks, in Namazi et al, 38 the authors considered the fractional diffusion equation to model and predict the effect of chemotherapy on cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…These applications cross diverse disciplines, such as chemical physics [1], viscoelasticity [2], electricity [3], finance [4], control theory [5], biomedical engineering [1], fluid mechanics [6] and other sciences (see [6,7,8] and references therein). In fact, it has been found that the fractional-order models are more adequate than the previously used integer-order models [9,10,11], because fractional-order derivatives and integrals enable the description of the memory and hereditary properties of different substances.…”
Section: Introductionmentioning
confidence: 99%